Developing a Triadic Implementation Framework for Adolescent HIV Status Disclosure in Resource-Limited Settings: A Mixed-Methods Study in Kenya - Obiero Ooko; Limkile Mpofu; Lawrence Mwaniki (Qualitative and Quantitative Research Center, 2026)
HIV status disclosure to adolescents living with HIV (ALHIV) remains a critical yet inconsistently implemented component of paediatric HIV care in resource-limited settings. Despite policy guidance promoting developmentally appropriate disclosure, routine practice continues to lag. This study formulates an evidence-informed triadic implementation framework grounded in empirical data and aligned with global guidelines. A convergent parallel mixed-methods design was conducted in Western Kenya, involving 310 caregiver–adolescent dyads, eight focus group discussions (n=64), and ten key informant interviews with healthcare providers. Multivariable logistic regression identified independent predictors of disclosure using a quadratic age term for non-linear dynamics, while thematic analysis explored contextual drivers across existing policy frameworks. Overall disclosure prevalence was 74.5%, but dropped to 1.8% among early adolescents (10–12 years), demonstrating a threshold effect (aOR=0.70, 95% CI: 0.59–0.83, p<0.001). Primary predictors included caregiver training (aOR=15.61), confidence (aOR=2.42), peer support access (aOR=3.33), and perceived adolescent maturity (aOR=1.52), whereas fear of psychological harm reduced disclosure odds (aOR=0.27). Disclosure was associated with improved ART adherence (93.9%) and emotional well-being (92.6%), despite initial distress (34.6%). The resulting Triadic Model conceptualizes disclosure as the convergence of adolescent readiness, caregiver capacity, and health system support. It operationalizes normative guidelines into five actionable mechanisms: structured readiness assessment, anticipatory caregiver preparation, family-engaged planning, health system enabling, and post-disclosure follow-up. This framework provides a scalable model to bridge the policy-practice gap in resource-constrained health systems.